A novel olfactory receptor gene family in teleost fish - Saraiva, Luis R.; Korsching, Sigrun I. (Genome Research, 2007)
While for two of three mammalian olfactory receptor families (OR and V2R) ortholog teleost families have been identified, the third family (V1R) has been thought to be represented by a single, closely linked gene pair. We identified four further V1R-like genes in every teleost species analyzed (Danio rerio, Gasterosteus aculeatus, Oryzias latipes, Tetraodon nigroviridis, Takifugu rubripes). In the phylogenetic analysis these ora genes (olfactory receptor class A-related) form a single clade, which includes the entire mammalian V1R superfamily. Homologies are much lower in paralogs than in orthologs, indicating that all six family members are evolutionarily much older than the speciation events in the teleost lineage analyzed here. These ora genes are under strong negative selection, as evidenced by very small dN/dS values in comparisons between orthologs. A pairwise configuration in the phylogenetic tree suggests the existence of three ancestral Ora subclades, one of which has been lost in amphibia, and a further one in mammals. Unexpectedly, two ora genes exhibit a highly conserved multi-exonic structure and four ora genes are organized in closely linked gene pairs across all fish species studied. All ora genes are expressed specifically in the olfactory epithelium of zebrafish, in sparse cells within the sensory surface, consistent with the expectation for olfactory receptors. The ora gene repertoire is highly conserved across teleosts, in striking contrast to the frequent species-specific expansions observed in tetrapod, especially mammalian V1Rs, possibly reflecting a major shift in gene regulation as well as gene function upon the transition to tetrapods.